Mechanical performance of consolidated crushed salt as backfill in boreholes and shafts - Supattra Khamrat; Kittitep Fuenkajorn (Songklanakarin Journal of Science and Technology (SJST), 2018)
Consolidation tests have been performed to determine the mechanical properties of crushed salt as affected by applied stresses and consolidation period. The crushed salt with particle sizes ranging from 0.075 to 4.76 mm mixed with 5% saturated brine are consolidated under axial stresses ranging from 2.5 to 10 MPa. The consolidation curves show instantaneous and transient creep strains. Densities, uniaxial compressive strengths and elastic moduli measured after consolidation for 3 to 180 days increase with the applied stresses and duration due to the particle rearrangement and recrystallization. The crushed salt properties are calculated as a function of mean strain energy required during consolidation. The opening depth and the time at which the crushed salt backfill is installed are significant factors controlling its long-term density, strength and stiffness.